Verbal encouragement in coaching: enhancing small-sided game performance in youth basketball players - Yılmaz, Osman; Jahrami, Haitham; Batalik, Ladislav; Trabelsi, Khaled; Ammar, Achraf; Soylu, Yusuf (Frontiers in Psychology, 2025)
BackgroundVerbal coach encouragement is a key motivational strategy that enhances skill development, game strategy execution, and team cohesion. In youth basketball, where players are still developing technical and decision-making abilities, coach encouragement can play a crucial role in sustaining effort, improving focus, and fostering resilience under small-sided games (SSGs). This study investigated how coach encouragement (CE) influences young basketball players’ technical performance and psychophysiological responses during competitive gameplay.MethodsSixteen male basketball players (age = 15.19 ± 1.05 years) voluntarily participated in the study. Heart rate, ratings of perceived exertion, mood states and technical activities were recorded with coach encouragement and without coach encouragement during SSGs.ResultsThe results showed that SSGs with coach encouragement were associated with significantly higher heart rate (p ≤ 0.05, d = 1.69), maximum heart rate percentage (p ≤ 0.05, d = 1.15), ratings of perceived exertion (p ≤ 0.05, d = 1.69), enjoyment (p ≤ 0.007, d = 0.86), technical abilities (e.g., successful passes and shots; p ≤ 0.05, d ranging from 1.08 to 1.25), and fatigue (p ≤ 0.03, d = 1.47).ConclusionThe findings of this study highlight the importance of CE in improving the psychophysiological and technical abilities of young basketball players during SSGs. CE improves coach-athlete relationships and increases game performance.